2013
DOI: 10.3922/j.psns.2013.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant effects of classical music on simvastatin induced reduction of anxiety but not object recognition memory in rats.

Abstract: Simvastatin is one of many hydroxymethylglutaryl-coenzyme-A reductase inhibitors that are prescribed to lower cholesterol. Some emerging evidence indicates that classical music can serve as an effective adjuvant in rats treated with simvastatin. Moreover, simvastatin and classical music have been shown to influence some cognitive functions. To further understand the mechanisms of action, we exposed rats to classical music for 1 month, and then treated them orally with simvastatin. The behavioral experiments su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 48 publications
(67 reference statements)
1
14
0
1
Order By: Relevance
“…Reduction of the availability of NMDA receptors to interact with NMDA or its physiological ligand glutamate is one mechanism that might mediate the anxiolytic activity of SIM. Our results also provide strong evidence that chronic high-dose SIM administration has NMDA antagonist-like effects, which would partially explain the anxiolytic effects of this drug (Camargo et al, 2013;Carrocini et al, 2012;Cruz et al, 2011;Pauleti et al, 2013;Santos et al, 2012).…”
Section: +supporting
confidence: 50%
See 2 more Smart Citations
“…Reduction of the availability of NMDA receptors to interact with NMDA or its physiological ligand glutamate is one mechanism that might mediate the anxiolytic activity of SIM. Our results also provide strong evidence that chronic high-dose SIM administration has NMDA antagonist-like effects, which would partially explain the anxiolytic effects of this drug (Camargo et al, 2013;Carrocini et al, 2012;Cruz et al, 2011;Pauleti et al, 2013;Santos et al, 2012).…”
Section: +supporting
confidence: 50%
“…It is well documented that NMDA receptors in the brain have a close correlation with anxiety-like activity (Bergink, van Megen, Westenberg, 2004;ChojnackaWójcik, Kłodzinska, Pilc, 2001). Modulation of NMDA receptors activity after SIM treatment could explain the drug's anxiolytic-like effects (Camargo et al, 2013;Carrocini et al, 2012;Cruz et al, 2011;Kilic et al, 2012;Pauleti et al, 2013;Santos et al, 2012;Wang et al, 2009;Yan et al, 2011). This hypothesis could be supported by the fact that altered levels of NMDA receptors in the hippocampus and amygdala directly influence anxiety behaviors (Barkus et al, 2010;Blundell, Adamec, 2007;Masneuf et al, 2014).…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…During the light and dark phases, the rats were exposed to light intensities of approximately 325 and 0.025 lux, respectively. These lux values were chosen because they were the light (Santos et al 2012, Camargo et al 2013). …”
Section: Subjectsmentioning
confidence: 99%
“…Current studies on the applications of statins have demonstrated their neuroprotective and clinical signifi cance among neurodegenerative diseases like cerebral ischemic stroke, vascular dementia, Alzheimer's disease, and Parkinson's disease, though the neuroprotective mechanisms are not completely understood (Vance 2012, Barone et al 2014, Moon et al 2014). There is a growing recognition that statins have pleiotropic effects beyond lowering cholesterol levels (Santos et al 2012, Camargo et al 2013.…”
Section: Introductionmentioning
confidence: 99%